A Bat-inspired Strategy for T-Way Interaction Testing - Kamal Z., Zamli; Alsariera, Yazan A. (American Scientific Publishers, 2015)
Combinatorial Interaction testing (or termed t-way testing) is a useful g strategy aimed at sampling a set of test cases from a large search space. As part of the strategy implementation, researchers have started to turn into meta-heuristic algorithms in line with the emergence of the new field called Search based Software Engineering. Complementing in the aforementioned respect, this paper discusses the adoption of Bat Algorithm as the basis of t-way strategy. Our experience has been promising as our strategy has managed to outperform many existing work, where the results of the experiment shows that BTS is superior in term of the solution quality.